THEORETICAL AND ANALYTICAL DISCOURSE OF THE CONCEPT OF PROFESSIONAL READINESS FOR FUTURE ACTIVITIES OF FUTURE MASTERS OF PSYCHOLOGISTS IN HIGHER EDUCATION INSTITUTIONS - Lariontseva, Anna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
Goal. The article is devoted to the theoretical and analytical analysis of aspects of the professional readiness of future masters for future activities in institutions of higher technical education. The theoretical principles of the professional readiness of the future psychologist for the future activity were considered, and the views of domestic and foreign scientists were analyzed regarding the professional readiness of the future masters of psychologists in institutions of higher technical education. Research methods. To achieve the goal, a set of methods and techniques of scientific knowledge were used in the work. Thus, to determine the essence of the concept of professional readiness, the methods that form the theoretical-analytical discourse of scientific and specialized literature on the problem of research and generalization of the obtained information are used; structural analysis; generalization of theoretical and methodological aspects of the problem; justification of the theoretical concept of the research subject; the method of logical generalization, which carries out a theoretical description of the importance of the tasks and clarification of the key concepts of the study. The results. The theoretical aspects of the concept of "professional readiness" for future activity are revealed, which form the basis of the formation of professional competencies of the future Master of Psychology in the process of preparation for his future professional activity. Conclusions. The problem of the professional readiness of master's psychologists for future professional activity is quite acute today, and the expansion of the field of activity of psychologists makes high demands on the personality of the specialist himself. The scale of the personality of the graduates of ZVTO should correspond to the scale of professional tasks that modern life and society pose to master psychologists, and this, at the same time, requires correction of educational programs in institutions of higher education